Implementación del ensayo de fatiga tipo tensión - compresión para mezclas asfálticas (2017)
In this investigation, two experimental set-ups for a tension - compression fatigue test on asphalt mixtures were evaluated. First, an initial approach of the trial was conducted on a existing set-up, obtaining satisfactory results and identifying the need for improvement of some aspects through another, more sophisticated, experimental equipment. The objective of the tests conducted on this second equipment was to conduct preliminary analyzes of the behavior of asphalt mixtures when subjected to repetitive load cycles at a constant deformation level. The typical loading scheme consisted on a load frequency of 10Hz at room temperature, applied to a cylindrical sample (D = 69 mm, and H = 130 mm). Two different test were conducted: the first was a deformation sweep test in order to identified the areas where the specimens failed, and the second was to select an intermediate deformation and to subject the sample to constant load cycles until the failure...